Analisis Pendapatan Usaha Ubi Bakar Cilembu di Ketapang - Novi Pebriani; Irfan Cholid; Assrorudin Assrorudin; Ira Arianti; Rois Indriawan (ISAS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a major role in boosting the regional economy and creating job opportunities. In Ketapang Regency, one of the growing businesses is Ubi Bakar Madu Cilembu Asli Sumedang owned by Mr. Tatang. The main challenge faced is the absence of proper financial records, so the owner does not yet clearly understand the amount of expenses, sales results, and whether the business is running profitably. This study aims to calculate total costs, production cost, total revenue, net profit, and the minimum sales volume required to avoid losses. This research uses a descriptive quantitative approach, collecting data through interviews, direct observation, and document review. The analysis is based on the principles of cost accounting and management accounting. The results show that the total monthly cost is IDR 43,495,666, the cost of producing one kilogram of product is IDR 27,185, total sales revenue reaches IDR 72,000,000, and the net profit earned is IDR 28,504,334. The business only needs to sell 238 kilograms per month to cover all costs, while actual sales are much higher. The benefit-cost ratio is 1.66, which indicates that this business is profitable and feasible for further development. Keywords: MSMEs, Production cost, Net profit, Break-even point, Business feasibility